Protection of children of divorced parents who are victims of emotional abuse - Batić Dragana; Akimovska-Maletić Iskra (Temida, 2011)
Very little is said and written about the problem of emotional abuse of children, as a result of parental divorce and separation, probably because it is a very sophisticated type of emotional abuse, which unfortunately sometimes experts do not recognize. This phenomenon is rarely explored and researched in general and especially in the Republic of Macedonia. It is not disputed that there is a solid legal framework for a government response to this type of child abuse in Republic of Macedonia. Given the impact on children, this problem requires much more attention, education and cooperation between the competent institutions. This paper tries to explore the concept of emotional abuse of children, as a result of divorce and separation of the parents, as a very specific form of domestic violence from a psychological point of view, as well as to analyze the legal norm of this form of domestic violence in the Republic of Macedonia.